2004
DOI: 10.1162/089892904323057317
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Prerequisites for Motion Blindness

Abstract: Neurobiological studies of visual awareness usually focus on the neural events elicited by perceived or nonperceived stimuli but neglect the preexisting conditions that allow (or prevent) conscious perception. We have examined the conditions that lead to temporary motion blindness in a rapid serial visual presentation paradigm, in which subjects have to detect coherent motion in the peripheral stream after a cue (a red fixation point) in the central stream. The failure of awareness depends critically on the oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
42
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(56 citation statements)
references
References 43 publications
10
42
4
Order By: Relevance
“…The study showed that both the motion N2 and the cognitive P300 component were reduced, but only the P300 showed a correlation with the psychophysical performance in individual trials, suggesting that sensory processing does not account for the impairment in coherence detection. This was confirmed by a second study, where Niedeggen et al [158] recorded VEPs to motion distractors to track sensory processing. In an experiment involving direction changes of two transparently moving surfaces, Rodríguez and Valdé s-Sosa [159] investigated how the occurrence of one stimulus affects the N2 recorded to a second stimulus that was presented shortly after the first one.…”
Section: Attention Task Effects and Interactions With Other Sensory mentioning
confidence: 65%
“…The study showed that both the motion N2 and the cognitive P300 component were reduced, but only the P300 showed a correlation with the psychophysical performance in individual trials, suggesting that sensory processing does not account for the impairment in coherence detection. This was confirmed by a second study, where Niedeggen et al [158] recorded VEPs to motion distractors to track sensory processing. In an experiment involving direction changes of two transparently moving surfaces, Rodríguez and Valdé s-Sosa [159] investigated how the occurrence of one stimulus affects the N2 recorded to a second stimulus that was presented shortly after the first one.…”
Section: Attention Task Effects and Interactions With Other Sensory mentioning
confidence: 65%
“…Using ERPs, we have been able to identify a neural correlate of this inhibitory mechanism. With increasing number of distractors, a frontal negativity (FN), peaking at about 250 msec after distractor onset, was found to be more expressed (Niedeggen, Hesselmann, Sahraie, Milders, & Blakemore, 2004). In a recent study on the attentional blink, a similar ERP component has been reported (Zhang, Zhou, & Martens, 2009).…”
Section: Introductionmentioning
confidence: 82%
“…Our model is in line with existing empirical evidence and provides specific predictions for future experiments that will be outlined below. Niedeggen, Hesselmann, Sahraie, Milders, and Blakemore (2004) recorded ERPs during a distractor-induced blindness paradigm and concluded that the inhibition of target perception occurs at a post-sensory level. In a later study, moreover, they showed that the inhibition causes an ERP EEG negativity over frontal cortical areas (Niedeggen et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, the model does not account for findings that the blindness effect increases in magnitude with increasing numbers of distractors (Hesselmann et al, 2006;Michael et al, 2011;Niedeggen et al, 2004Niedeggen et al, , 2012. Moreover, the current implementation of the reset pulse that terminates reverberation of activity in the closed frontal loop is of a rather abstract nature as it is evoked from outside the model rather than originating from model dynamics.…”
Section: Limitations and Future Directionsmentioning
confidence: 94%